Meeting Diverse Learning Needs: Exploring Effective Sociology Teacher Strategies in Differentiated Learning - Octamaya Tenri Awaru, A.; Ridwan Said Ahmad, M.; Sadriani, Andi; Fajri Maulana, Muh. (KnE Social Sciences, 2024)
A major challenge for sociology teachers is to teach students the complex sociology subject matter based on their learning needs. The purpose of this study is to explore the strategies used by sociology teachers in applying differentiated learning at the high school level in Makassar City. This research is a qualitative research that uses teachers and students as research informants. Data were collected through interviews, observations, and documentation. Data analysis was done through the stages of data collection, data reduction, and data presentation. Results show that sociology teachers in Makassar City have implemented effective strategies for differentiated learning. These include the use of diverse learning resources other than textbooks, namely audiovisual materials in the form of videos and presentation slides; visual materials in the form of infographics, images, and maps; utilizing relevant articles from blogs and research articles; and initial assessments to identify students’ individual needs in the form of questionnaire filling, diagnostic tests, and pretests. Group formation is flexible based on the student’s ability and group members are rotated in each meeting, applying various learning methods and models, such as problem-based learning, and combining it with cooperative learning models. The teachers also provide additional support in the form of having discussions with students, answering their questions, assigning different assignments, and providing additional material. The findings of this research are expected to contribute to developing different learning approaches, especially in sociology subjects. Keywords: differentiated learning, sociology, strategy